Personal Identity of Senior Pupils in Connection with Their Cognitive Motives - Zuiev, Ihor; Beliaeva, Karina; Milanina, Anastasiia (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2022)
The aim of the work is to study the personal identity of senior pupils in connection with their cognitive motives. Identity is considered an awareness of self-identity, integrity, and continuity of a person. The development of personal identity is understood as a process of constant awareness of one’s uniqueness, authenticity, and originality. It was empirically found that in senior pupils with low levels of cognitive motives, the reflexive “self” and the physical “self” prevail, and in pupils with high levels of cognitive motives, physical and active “selves” prevail. “Pseudoidentity” as a status prevails among the respondents. For the pupils with a low level of cognitive motive, a “diffuse identity” is typical, and for those with a high level of cognitive motive, a “moratorium” is typical, i.e., an identity crisis, which is accompanied by a desire to actively solve life’s challenges, determine themselves and use various behaviors for those purposes. It has been found that in pupils with a low level of cognitive motive, the formation of an active “self” is connected with the “premature identity”, and in those with a high level - with the “gained (genuine) identity”. The cognitive motive may be a positive factor in developing self-identity in senior pupils.